DEVELOPMENT OF THE SECOND PRELIMINARY ITEM POOL OF THE LATVIAN CLINICAL PERSONALITY INVENTORY: AN INTEGRATIVE APPROACH - Perepjolkina, Viktorija; Koļesņikova, Jeļena; Mārtinsone, Kristīne; Stepens, Ainārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
On the moment, there is a lack of available clinical personality assessment instruments in Latvia, so in the frame of the National Research Programme (2014-2017, project No. 5.8.2.) a new multi-item multi-scale self-report measure - the Latvian Clinical Personality Inventory (LCPI) is currently being developed. LCPI structure includes three parts: clinical scales, pathological personality scales and functioning scales and will provide a possibility to perform a combined analysis of mental disorders symptoms and functioning aspects using one clinical personality inventory. The main aim of this article to describe procedures and stages of the development of the preliminary version of the LCPI v2.2. item pool.